(80-x)+(90-2x)=180

Simple and best practice solution for (80-x)+(90-2x)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (80-x)+(90-2x)=180 equation:


Simplifying
(80 + -1x) + (90 + -2x) = 180

Remove parenthesis around (80 + -1x)
80 + -1x + (90 + -2x) = 180

Remove parenthesis around (90 + -2x)
80 + -1x + 90 + -2x = 180

Reorder the terms:
80 + 90 + -1x + -2x = 180

Combine like terms: 80 + 90 = 170
170 + -1x + -2x = 180

Combine like terms: -1x + -2x = -3x
170 + -3x = 180

Solving
170 + -3x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-170' to each side of the equation.
170 + -170 + -3x = 180 + -170

Combine like terms: 170 + -170 = 0
0 + -3x = 180 + -170
-3x = 180 + -170

Combine like terms: 180 + -170 = 10
-3x = 10

Divide each side by '-3'.
x = -3.333333333

Simplifying
x = -3.333333333

See similar equations:

| x^2-x=23 | | 79=-5(2x+3)-7(-4+8x) | | 12x+13=56 | | 12+x(13)=12 | | 6(3x-8)=14x-20 | | 3z^2-13z+4=0 | | z^2-10z+9=0 | | -29=592a-1+2a | | 2x+1x+1x=500000 | | 5x+40+2x=180 | | -9n(7n-6)=0 | | 2x+1x+1x=900000 | | 6x=-6x-3(5-3x) | | (4x-12)(7x+6)=0 | | (4x-12)(7x+6)=0 | | 3x+1x+1x=900000 | | 27x^2+12=36x | | 67=N-84 | | N+6=15 | | 3(d+2e)-11d= | | k-(-8k)= | | 3*(2x-4)=24 | | 48-3x=15x+22 | | 2d-5-3d-8= | | -3p+5p= | | -32-3w-5w=0 | | 8t+t= | | 2*(2x-4)=24 | | 6x+2y=22 | | 2*(2x+3)=3*(x+10) | | 8a+2=6-10a | | -6x+4=1 |

Equations solver categories